Effects of Mandibular Extension on Pial Arteriolar Diameter Changes in Glucocorticoid-Induced Hypertensive Rats - Lapi, Dominga; Varanini, Maurizio; Galasso, Lucrezia; Di Maro, Martina; Federighi, Giuseppe; Del Seppia, Cristina; Colantuoni, Antonio; Scuri, Rossana (Frontiers in Physiology, 2019)
Previously, in normotensive rats, it has been observed that a repetitive sub-maximal mouth opening obtained by placing a home-made U-shaped dilator between the superior and inferior dental arches of the rat (ME), induced a particular modulation of pial arteriolar tone. In the present study we studied the geometric characteristics of pial microcirculation in two different cerebral regions and the hemodynamic effects of a single or double ME on pial arteriolar rhythmic diameter changes in rats rendered hypertensive by dexamethasone administrations. Cranial windows were prepared on parietal and frontal region. Pial arterioles were classified by Strahler method in five orders by in vivo fluorescence microscopy technique associated with a computerized system that permits off-line measurements of arteriolar diameter changes. Two 10 min ME at 10 min interval were applied; then the animals were monitored for further 240 min. Dexamethasone-treated rats exhibited a marked arterial rarefaction and asymmetry of bifurcation in the arteriolar networks that resulted more evident in the frontal region. Starting from ME1, in both cortical areas, the arterioles dilated, and the vasodilation became significant compared to baseline after ME2 for the entire observation period. The spectral analysis carried out in order 2 arterioles showed that a double ME re-activated the frequency components related to endothelial, neuronal and myogenic activity in both the cortical regions studied. In conclusion, a double ME has a generalized effect in the cortical areas by restoring the physiological vasomotion of the pial arterioles that was severely impaired by the experimentally hypertension.